Models for innovation diffusion - Mahajan, Vijay. (Quantitative applications in the social sciences, 1985)
The intellectual environment surrounding diffusion models has been restricted by the language and notation employed in different fields. It's a topic which begs for a sound intellectual introduction. This book provides that introduction, bridging disciplines and setting out findings in a clear and consistent way.